2020
DOI: 10.1155/2020/5454210
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Alleviates Lipopolysaccharide-Induced Acute Kidney Injury by Inhibiting p75NTR-Mediated Oxidative Stress and Apoptosis

Abstract: Oxidative stress and apoptosis play a key role in the pathogenesis of sepsis-associated acute kidney injury (AKI). Dexmedetomidine (DEX) may present renal protective effects in sepsis. Therefore, we studied antioxidant effects and the mechanism of DEX in an inflammatory proximal tubular epithelial cell model and lipopolysaccharide- (LPS-) induced AKI in mice. Methods. We assessed renal function (creatinine, urea nitrogen), histopathology, oxidative stress (malondialdehyde (MDA) and superoxide dismutase (SOD)),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 60 publications
1
47
0
Order By: Relevance
“…Lipopolysaccharide is widely used for SA-AKI induction in mice ( 12 ). We verified its efficacy by injecting 10 mg/kg of LPS (dissolved in 0.9% saline) into mice, intraperitoneally.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipopolysaccharide is widely used for SA-AKI induction in mice ( 12 ). We verified its efficacy by injecting 10 mg/kg of LPS (dissolved in 0.9% saline) into mice, intraperitoneally.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies chose to switch to in vitro experiments to eliminate these potential confounders. Most studies have been carried out using proximal tubular epithelial cells to study the toxicity of LPS ( 12 ). However, the kidney is made up of a variety of cell types, including but not limited to podocytes, proximal tubular cells, loops of Henle cells, distal tubular cells, and collecting duct cells.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory response has been known as key mechanism underlying aortic dissection. The upregulation of cytokines, endothelial adhesion molecules or chemokines are found to play a role in multiple organ injury, including myocardial ischemic injury, acute kidney injury and gastrointestinal disorders (23)(24)(25)(26)(27)(28). These data led us to speculate that immune cells are important to the postoperative organ injury in AAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are few epidemiological studies of sepsis-caused AKI. Present studies have shown that its fatality rate is as high as 70%, which is significantly higher than that of sepsis patients without organ damage (Wang et al, 2020). If timely and effective intervention can be implemented in the early stage of AKI in 2015).…”
Section: Discussionmentioning
confidence: 95%